CORPORATE SIZE, PROFITABILITY AND MARKET VALUE: AN ECONOMETRIC PANEL ANALYSIS OF LISTED FIRMS IN KENYA - Mule, Robert Kisavi; Mukras, Mohamed Suleiman; Nzioka, Onesmus Mutunga (European Scientific Journal, ESJ, 2015)
In corporate finance, the size of a firm is a primary factor in determining the success of a firm due to economies of scale. While, previous studies have confined their analyses on either a single industry or a few firms, in this study, we consider a rather comprehensive sample of firms that represent a sufficiently broad range of firm sizes in all sectors of Kenyan economy hence amplifying the importance of the study. Global corporate size literature shows plausable but mixed relationship between firm size, profitability and market value. The effect of corporate size on profitability and market value in a frontier market using panel methodology is unknown. The purpose of this study is to explore the effect of corporate size on profitability and market value of listed firms in Kenya. In this study, data for companies which were active in Nairobi Securities Exchange (NSE) between the years 2010 to 2014 has been used. Unit root test results indicate that all the variables are integrated of order zero (p = .000) meaning that they were stationary at levels. Panel correlation and multiple regression methods are used in the empirical estimations. Results indicate that there is a positive significant relationship between firm size and profitability, that is, return on equity (Î² = .012, t = 2.585) impying that value that a unit change in firm size leads to an increase in return on equity of firms listed at the Nairobi Securities Exchange of 0.012, all things being fixed whereas firm size insignificantly positively predicts profitability, that is, return on asset (Î² =.012, t = 1.659). In addition, the results show that corporate size has no statistically significant impact on firm market value (Î² = -.011, t = -.225) under random effects specification.